The nested variant of urothelial carcinoma arising in a fibroepithelial polyp: Report of a case and review of literature - Nadira Mamoon; Zujajah Hameed; Fazal Ilahi; Imran Nazir Ahmad (Indian Journal of Urology, 2014)
The nested variant of urothelial carcinoma is a rare but very important histological entity due to its deceptively bland-looking appearance and aggressive behavior. We present a case of a 30-year-old man who was found to have a solitary polypoid growth in the bladder. It was resected and found to be a fibroepithelial polyp; a rare entity in itself, harboring the above tumor. The lesion also showed a second population of scattered bizarre stromal cells. To our knowledge, this is the first instance of a nested variant of urothelial carcinoma arising in a fibroepithelial polyp. The presence of atypical stromal cells has also not been described previously.